CONVERSATIONAL AI DIALOGUE SYSTEMS, CONVERSATIONAL AGENTS,AND CHATBOATS - MICHAEL MCTEAR (New Jersey MORGAN AND CLAYPOOL PUBLISHERS, 2021)
ARTIFICIAL INTELLIGENCE,NATURAL LANGUAGE PROCESSING ,HUMAN COMPUTER INTRERACTION AND CONVERSATIONAL AI
CONVERSATIONAL AI
COMPUTERS
Keywords: ARTIFICIAL INTELLIGENCE; COMPUTERS